Do aparelho estatal ao interesse público: crise e mudança de paradigmas na produção técnico-científica em administração pública no Brasil (1937-1997): análise de conteúdo dos artigos publicados na Revista do Serviço Público (1937-...) e Revista de Administração Pública (1967-...) - Keinert, Tania Margarete Mezzomo (1999)
This work analyses the writings on Public Administration in Brazil made by academicians between 1937 and 1997. The content analysis of the articles published by Revista do Serviço Público (Civil Service Review) - 1937 up today - and Revista de Administração Pública (Public Administration Journal) - 1967 up today - reveals that the concept of public changes its meaning from the ‘Public as State Paradigm’ to the emergent ‘Public as Public Interest Paradigm’.